2011
DOI: 10.1128/aem.02677-10
|View full text |Cite
|
Sign up to set email alerts
|

The Swarming Motility of Pseudomonas aeruginosa Is Blocked by Cranberry Proanthocyanidins and Other Tannin-Containing Materials

Abstract: Bacterial motility plays a key role in the colonization of surfaces by bacteria and the subsequent formation of resistant communities of bacteria called biofilms. Derivatives of cranberry fruit, predominantly condensed tannins called proanthocyanidins (PACs) have been reported to interfere with bacterial adhesion, but the effects of PACs and other tannins on bacterial motilities remain largely unknown. In this study, we investigated whether cranberry PAC (CPAC) and the hydrolyzable tannin in pomegranate (PG; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
180
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 226 publications
(188 citation statements)
references
References 39 publications
6
180
0
2
Order By: Relevance
“…Although a statistically significant reduction in S. aureus biofilm growth was seen with keracyanin, it is unclear whether this small decrease (Ͻ1 log) in vitro would result in clinically significant biofilm reduction in vivo. Cranberry proanthocyanidins, another flavonoid class, were previously shown to have antibiofilm properties 76 and block P. aeruginosa swarming, 77 which indicates that they may be more useful as therapeutics than anthocyanidins.…”
Section: Discussionmentioning
confidence: 99%
“…Although a statistically significant reduction in S. aureus biofilm growth was seen with keracyanin, it is unclear whether this small decrease (Ͻ1 log) in vitro would result in clinically significant biofilm reduction in vivo. Cranberry proanthocyanidins, another flavonoid class, were previously shown to have antibiofilm properties 76 and block P. aeruginosa swarming, 77 which indicates that they may be more useful as therapeutics than anthocyanidins.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study,tannins of cranberry fruit and the hydrolysable tannin in pomegranate were reported to inhibit swarming motility but did not block swimming or twitching motilities (51). Sub-inhibitory concentrations of alkaloids like piperine of black pepper and reserpine of snakeroot, decreased bacterial swarming and swimming motilities (52). Tannic acid and epigallocathecingallate were found to block swarming motility in Pseudomonas aeruginosa (53).…”
Section: Biofilms Are Formed On Surfaces Of Living Tissues Medical Dmentioning
confidence: 99%
“…The plate was pointinoculated with an overnight culture of PAO1 once the overlaid agar had solidifi ed, and incubated at 37°C for 3 days. The extent of swarming was determined by measuring the area of the colony (16) . The experiment was performed in triplicate and repeated twice.…”
Section: Swarming Assaymentioning
confidence: 99%